Enhancement of TRP Gene Expression and UV Absorption by Bioconverted Chestnut Inner Shell Extracts Using Lactiplantibacillus plantarum - So-Hee Kim; Suh-Hee Yoem; Jun-Hee Kim; Ji-Woo Hong; Ye-Sol Oh; Jin-Woo Kim (Molecules, 2022)
In this work, the suppression of tyrosinase-related genes, including an improvement in UV absorption effects of bioconverted CS extracts (BCS), was investigated to improve the skin-whitening effect. Total polyphenols and total flavonoids, which are bioactive components, increased 2.6- and 5.4-times in bioconversion using Lactiplantibacillus plantarum SM4, respectively, as compared to ultrasound-assisted extracts (UCS). The effect of BCS on radical scavenging activity, UV-A absorption, and tyrosinase activity inhibition, contributing to skin-whitening, were 1.3-, 1.2-, and 1.2-times higher than those of UCS, respectively. The main component identified in high-performance liquid chromatography (HPLC) was gallic acid in both UCS and BCS, which increased by 2.9-times following bioconversion. The gene expression of tyrosinase-related proteins, including TRP-1 and TRP-2 genes, was studied to confirm the suppression of melanin synthesis by BCS in order to identify the skin-whitening mechanism, and BCS decreased both genes’ expression by 1.7- and 1.6-times, demonstrating that BCS effectively suppressed melanin synthesis. These findings imply that the chestnut inner shell can be employed as a cosmetic material by simultaneously inhibiting melanogenesis and enhancing UV-A absorption through bioconversion using L. plantarum SM4.